2012
DOI: 10.1021/mp3003336
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of mRNA Lipoplexes by Dendritic Cells

Abstract: Lipoplexes, composed of Lipofectamine and mRNA encoding HIV Gag protein, were shown to be internalized by dendritic cells (DCs) and promote antigen presentation to stimulate HIV-specific T cell responses. Using confocal microscopy, we showed that one-third of fluorescently labeled mRNA containing lipoplexes are colocalized with late endosomes. We further investigated the effect of inhibitors, blocking phagocytosis, macropinocytosis, and clathrin- and caveolae-mediated endocytosis, on both the internalization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…The overall data suggest that several endocytic pathways are involved in the uptake and intracellular delivery of siRNA during Lipofectamine transfection, which is supported by available literature. 47,48 The reduction in gene silencing activity of the siRNA/cSCKs complexes was unclear for all the inhibitors used, probably due to the low transfection of the cSCKs themselves, and hence, it was difficult to observe the reduction in transfection. A slight increase in transfection of cSCKs upon pre-treatment with CP was observed (not significant, p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The overall data suggest that several endocytic pathways are involved in the uptake and intracellular delivery of siRNA during Lipofectamine transfection, which is supported by available literature. 47,48 The reduction in gene silencing activity of the siRNA/cSCKs complexes was unclear for all the inhibitors used, probably due to the low transfection of the cSCKs themselves, and hence, it was difficult to observe the reduction in transfection. A slight increase in transfection of cSCKs upon pre-treatment with CP was observed (not significant, p > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Replicon RNA has been delivered by coating on to gold microparticles [ 26 ], but these are neither biodegradable nor nanoparticles, and do not offer the advantages of biodegradable nanoparticles for targeting DCs and processing via DC endocytic pathways. While mRNA delivery to DCs has proven successful [ 27 , 28 , 29 , 30 , 31 , 32 ], it has only recently been shown that such nanoparticulate delivery is feasible for the much larger RepRNA molecules [ 33 ] ( Figure 2 and Figure 3 ). This success of nanoparticle-based delivery of RepRNA to DCs requires an appreciation of the DC requirements for interaction with the delivery vehicles and the subsequent intracellular delivery of the RepRNA to the RNA translation sites ( Figure 3 ).…”
Section: The Self-amplifying Replicon Rnamentioning
confidence: 99%
“…Such an observation cannot be repeated with an RNase-sensitive pestivirus RepRNA, which does not lead to translation or induction of immune responses in vitro or in vivo when employed as “naked” RNA [ 33 ]. These observations may relate to the application of mRNA vaccines applied as “naked” RNA; such vaccines require capping and/or poly-adenylation [ 1 , 28 , 91 , 92 , 93 ]. It has been well established for over two decades that alphavirus RNAs contain 5' hypermethylated caps, together with a 3' poly(A) tail in their genomic structure [ 94 ].…”
Section: Reprna Delivery By Nanoparticulate Vehicles Induces Immumentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, non-viral vectors availing nanotechnological advances are in the focus of investigation to improve cellular uptake and subsequent transfection of target cells. Therefore, a variety of different biocompatible and biodegradable nanoparticles (NPs) have been developed including lipid-based [ 4 7 ] and polymer-based [ 8 , 9 ] systems, featuring a cationic surface charge and thereby facilitating complexation of anionic mRNA. While these approaches rendered significant progress to overcome drawbacks resulting from mRNA-based delivery in vitro as well as in vivo [ 10 13 ], designing of suitable systems with low cytotoxicity and high transfection rate [ 14 ] remains crucial parameters and sets an indispensable precondition for mRNA-delivery.…”
Section: Introductionmentioning
confidence: 99%